2020
DOI: 10.1038/s12276-019-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

The USP21/YY1/SNHG16 axis contributes to tumor proliferation, migration, and invasion of non-small-cell lung cancer

Abstract: Deubiquitinases (DUBs) and noncoding RNAs have been the subjects of recent extensive studies regarding their roles in lung cancer, but the mechanisms involved are largely unknown. In our study, we used The Cancer Genome Atlas data set and bioinformatics analyses and identified USP21, a DUB, as a potential contributor to oncogenesis in non-small-cell lung cancer (NSCLC). We further demonstrated that USP21 was highly expressed in NSCLCs. We then conducted a series of in vitro and in vivo assays to explore the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 55 publications
3
53
1
Order By: Relevance
“…Chen et al reported that USP21 enhanced the metastatic and proliferative ability of bladder cancer by regulating EZH2 27 . Xu et al showed that the USP21/YY1/SNHG16 axis enhances the progression of NSCL 28 . A study by Liu et al found that lncRNA FGD5-AS1 regulates oral squamous cell carcinoma progression by interacting with the miR-520b/USP21 axis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that USP21 enhanced the metastatic and proliferative ability of bladder cancer by regulating EZH2 27 . Xu et al showed that the USP21/YY1/SNHG16 axis enhances the progression of NSCL 28 . A study by Liu et al found that lncRNA FGD5-AS1 regulates oral squamous cell carcinoma progression by interacting with the miR-520b/USP21 axis 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We showed that USP21 is also amplified in prostate cancer CTCs. USP21 amplification can increase proliferation, migration, and invasion [ 64 ]. In non-small-cell lung cancer (NSCLC), USP21 amplification is highly prevalent and it is speculated that inhibition of USP21 might serve as a promising therapeutic approach in NSCLC [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 These results suggest that YY1 might be a potential target for tumor progression. In lung cancer, Xu et al indicate that the USP21/YY1/ SNHG16 axis contributes to tumor proliferation, migration, and invasion of nonsmall-cell lung cancer 23 ; and Li et al reveal that YY1 accelerates angiogenesis and progression in lung cancer through enhancing long noncoding RNA MCM3AP-AS1 expression. 24 Our work indicates that YY1 is necessary for hypoxia-induced stemness of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%